Discovery Tool vs. PubMed: A Health Sciences Literature Comparison Analysis - Ketterman, Elizabeth; Inman, M.E. (My University, 2014)
The East Carolina University libraries, though administratively separate, jointly subscribe to and collaborate on enhancements for a shared instance of the Summon Discovery Service. Based on usage, enhancements to the discovery tool over the past few years, and the perceived ease of searching in Summon, health sciences librarians have questioned whether Summon could now be considered a legitimate competitor to PubMed. This article includes results of a citation comparison between the two databases and the conclusion that Summon produces quality results, but should not be considered an adequate replacement information source for a subject-specific database like PubMed.
Keywords: discovery; Summon; PubMed; citation analysis; comparison analysis; health sciences libraries